Thinking Beyond Field to Fork - Potter, Charlotte (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Farmers make management decisions at every step of the crop’s production process, from tilling land to prepare for planting, to managing a field after harvest, and every decision impacts sustainability. As the cost to produce our food rises, farmers are looking for new Best Management Practices both on-farm and off to help them manage and survive. Given the scale and impact of resource-intensive industrial agriculture, to meet our sustainability goals, significant changes in food production are needed. But what should those changes look like?